Epidemiological Characteristics of COVID-19 and Effective Public Health Interventions in Shenzhen, China - Li, Guiyu; Lin, Jiyong; Xu, Danping (Frontiers in Public Health, 2022)
Objectives: This study aims to analyze and summarize the epidemic characteristics of coronavirus disease 2019 (COVID-19), and the public heath interventions in Shenzhen from 1 January 2022 to 4 April 2022, hoping to provide useful reference for resurgence. Methods Data were extracted from the website of Shenzhen Municipal Health Commission from 1 January 2022 to 4 April 2022. The number of new indigenous patients, imported patients, symptomatic and asymptomatic patients, age, gender, regional distribution, screening routes, and clinical subtype were analyzed. The public health interventions were summarized and described. Results There have been 1,215 new indigenous cases and 1,447 imported cases in Shenzhen from 1 January 2022 to 4 April 2022. The age group of the indigenous cases range from 2 months to 92 years. The median age was 35.0. The male-to-female ratio was 1.13 (623:551). The number of symptomatic and asymptomatic patients were 930 (76.5%) and 285 (23.5%), respectively, without death. Shenzhen has experienced three outbreaks. Futian District has the large proportion of confirmed cases (55.8%), followed by Nanshan (13.5%), and Baoan District (13.5%). The indigenous confirmed cases were mainly screened from close contacts under quarantine observation (632 cases, 53.8%), key areas (304 cases, 25.9%), key crowds (93 cases, 7.9%), and communities (145, 12.4%). Among the imported cases outside the Chinses Mainland, China's Hong Kong had the largest number of confirmed cases (n = 1,368), followed by Singapore (n = 18), South Korea (n = 18), and Japan (n = 14). The Shenzhen government quickly implemented effective measures, including citywide screening, quarantine, tracking, classified management for different groups and the dividing epidemic-hit communities, villages into three regions (sealed area, controlled area, and prevention area), and expand the capacity of designated hospitals, etc., which effectively controlled the outbreaks. By 4 April 2022, no new local cases had been reported. Conclusions Three novel COVID-19 outbreaks occurred in Shenzhen between 1 January to 4 April 2022, linked to importation from outside the Chinese Mainland and subsequently caused the local transmission. The measures of citywide testing–tracking–classified management by risk level have effectively controlled the epidemic and should be continued to prevent resurgence.